2018
DOI: 10.1016/j.radonc.2018.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SUVmax and SUVpeak based segmentation to determine primary lung tumour volume on FDG PET-CT correlated with pathology data

Abstract: No benefit was shown on clinical data for the SUVpeak based segmentation method over a SUVmax based one. Both methods can be used to determine the tumour volumes in resected NSCLC tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…Most of these previous studies exploited arbitrary values of %SUV max image thresholds, despite the well-established limited accuracy and robustness of such methodology for the segmentation of PET image based functional volumes 1316 . Indeed, optimal threshold values greatly depend on lesion size and contrast 17 , in addition to being very challenging to determine in case of high intratumor uptake heterogeneity where relationship between maximum intensity and overall contrast can be quite different than for homogeneous lesions. A recent MICCAI challenge further highlighted these limitations, as both implemented fixed thresholds (40 and 50% of the maximum) were amongst the worst ranked methods 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Most of these previous studies exploited arbitrary values of %SUV max image thresholds, despite the well-established limited accuracy and robustness of such methodology for the segmentation of PET image based functional volumes 1316 . Indeed, optimal threshold values greatly depend on lesion size and contrast 17 , in addition to being very challenging to determine in case of high intratumor uptake heterogeneity where relationship between maximum intensity and overall contrast can be quite different than for homogeneous lesions. A recent MICCAI challenge further highlighted these limitations, as both implemented fixed thresholds (40 and 50% of the maximum) were amongst the worst ranked methods 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Mercieca et al ., in a study of 30 patients, demonstrated that the mean optimal percentage threshold of 47% ± 10% of SUV max based tumor volume correlated best with the pathological tumor volume. [ 17 ] The optimal threshold of the above two studies closely matches our optimal threshold of 36%, and the difference could possibly be because we used the largest tumor dimension rather than tumor volume. van Loon et al .…”
Section: Discussionmentioning
confidence: 75%
“…[ 4 15 ] However, very few published studies compared auto delineated maximum tumor dimension with the pathological tumor size of surgical specimens, which is considered to be the gold standard. [ 4 14 17 ] PET/CT based tumor volume corresponds more accurately to the pathological tumor volume as compared to the CT based tumor. [ 4 ] Furthermore, tumor delineation using PET/CT improves precision, especially in poorly defined tumors and reduces interobserver variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations